The Influence of Price and Product Quality on Purchasing Decisions (Case Study of Eld Store Online Business) - AL-Ayubi, Hamim; Sari, Sukarni Novita (Logistica : Journal of Logistic and Transportation, 2023)
The purpose of this study was to find out and analyze the effect price and product quality on purchasing decisions. The study used a quanttative method ith a population of 19,400 samples before then 100 samples were obtained. The research results showed that on the atitude variable, the tcount value 9495 > the table value 1.984, then the attitude variable is declared to have a positive effect. So it can be concluded that the hypothesis that price affects purchasing decisions is accepted. The count value 6 270 > the table value 1.984, therefore, based on he calculation results, & can be concluded that the hypothesis that product quality affects purchasing decisions is acoepted. Simutaneous test (F-test) that was carried out resulted in Fcount of 44,709 which means that the independent variable has a signifcant relationship to the dependent variable, with a signicance value of o.000. So, the hypothesis that the price and product qualty atfect purchasing decisions is accepted. There is a signficant effect of the price and product quality variables on purchasing decisions by 48% on the other hand, 52% of purchasing decisions are influenced by other factors.